Glutathione levels in and total antioxidant capacity of Candida sp. cells exposed to oxidative stress caused by hydrogen peroxide - Abegg,Maxwel Adriano (2012)
INTRODUCTION: The capacity to overcome the oxidative stress imposed by phagocytes seems to be critical for Candida species to cause invasive candidiasis. METHODS: To better characterize the oxidative stress response (OSR) of 8 clinically relevant Candida sp., glutathione, a vital component of the intracellular redox balance, was measured using the 5,5'-dithiobis-(2-nitrobenzoic acid (DTNB)-glutathione disulfide (GSSG) reductase reconversion method; the total antioxidant capacity (TAC) was measured using a modified method based on the decolorization of the 2,2'-azinobis-(3-ethylbenzothiazoline-6-sulfonic) acid radical cation (ABTS*+). Both methods were used with cellular Candida sp. extracts treated or not with hydrogen peroxide (0.5 mM). RESULTS: Oxidative stress induced by hydrogen peroxide clearly reduced intracellular glutathione levels. This depletion was stronger in Candida albicans and the levels of glutathione in untreated cells were also higher in this species. The TAC demonstrated intra-specific variation. CONCLUSIONS: Glutathione levels did not correlate with the measured TAC values, despite this being the most important non-enzymatic intracellular antioxidant molecule. The results indicate that the isolated measurement of TAC does not give a clear picture of the ability of a given Candida sp. to respond to oxidative stress.